2020
DOI: 10.3390/vaccines8040668
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Impact of SARS-CoV-2 Vaccination: Mathematical Modeling Analyses

Abstract: This study aims to inform SARS-CoV-2 vaccine development/licensure/decision-making/implementation, using mathematical modeling, by determining key preferred vaccine product characteristics and associated population-level impacts of a vaccine eliciting long-term protection. A prophylactic vaccine with efficacy against acquisition (VES) ≥70% can eliminate the infection. A vaccine with VES <70% may still control the infection if it reduces infectiousness or infection duration among those vaccinated who acquire… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
79
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 51 publications
7
79
0
Order By: Relevance
“…Mathematical modeling played an influential role in guiding the national public-health response by characterizing and understanding the epidemic, forecasting health care needs, predicting the impact of social and physical distancing restrictions, and rationalizing and justifying the easing of restrictions. While this article illustrates a successful case study, the modeling tools employed here can be adapted and applied in other countries to guide SARS-CoV-2 epidemic control, preparedness for the current or future waves of infection, or enforcement and easing of restrictions or other interventions, such as vaccination [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mathematical modeling played an influential role in guiding the national public-health response by characterizing and understanding the epidemic, forecasting health care needs, predicting the impact of social and physical distancing restrictions, and rationalizing and justifying the easing of restrictions. While this article illustrates a successful case study, the modeling tools employed here can be adapted and applied in other countries to guide SARS-CoV-2 epidemic control, preparedness for the current or future waves of infection, or enforcement and easing of restrictions or other interventions, such as vaccination [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Building on our previously developed models [ 8 , 18 - 21 ], an age-structured, meta-population, deterministic mathematical model was constructed to describe SARS-CoV-2 transmission dynamics and disease progression (Figure S1 in the Online Supplementary Document ). The model stratified the Qatari population into groups (“compartments”) according to the major nationality groups (Indians, Bangladeshis, Nepalese, Qataris, Egyptians, Filipinos, and all other nationalities), age group by decile, infection status (infected, uninfected), severity of illness (asymptomatic/mild, severe, critical), and disease/hospitalization stage (severe, critical), using sets of coupled, nonlinear, differential equations.…”
Section: Methodsmentioning
confidence: 99%
“…These estimates are in line with current modeling efforts with large SEIR models. 17 Therefore, after a vaccine becomes available, we allow R(t) to decrease linearly over 1 year to reach levels of herd immunity or R(t)~0. 8 In total, we account for the growth in infections from the index infection date over the next 15 months, with each new infection experiencing the probabilistically similar QALY loss for the patient and their family members as our index case.…”
Section: Methodsmentioning
confidence: 99%
“…Since the primary endpoint of the vaccine’s randomized clinical trials was efficacy of the vaccine against laboratory-confirmed COVID-19 cases [ 6 , 7 , 8 ], and not just any infection, documented or undocumented, it is unknown whether the vaccine prophylactically reduces susceptibility to the infection (that is, efficacy defined as the proportional reduction in the susceptibility to infection among those vaccinated compared to those unvaccinated [ 5 ]) or whether it just reduced serious symptomatic COVID-19 cases with no effect on infection (that is, efficacy against disease progression, defined as the proportional reduction in the fraction of individuals with severe or critical infection among those vaccinated but who still acquired the infection compared to those unvaccinated [ 5 ]). These two mechanisms of action bracket the two extremes for the vaccine’s biological effect, with the former mechanism being the most optimistic (reducing both infection and disease) and the latter being the most pessimistic (reducing only disease).…”
Section: Methodsmentioning
confidence: 99%
“…We previously developed a mathematical model to investigate the generic population-level impact of SARS-CoV-2 vaccination [ 5 ]. In light of recently produced vaccines with ~95% efficacy against Coronavirus Disease 2019 (COVID-19) symptomatic disease [ 6 , 7 ], the model was extended to assess the impact of these novel vaccines on COVID-19 morbidity and mortality in two major countries at different epidemic phases, the United States (US) and China.…”
Section: Introductionmentioning
confidence: 99%